The Effect of Communication, Information, Education on the Knowledge Level of Acceptors about Side Effects of 3-Month Contraceptive Injection at BPM L Banjaranyar Village - Safira Rizky M; Wulan Margiana (Proceedings Series on Health & Medical Sciences, 2021)
The increasing world population will cause many problems in various fields, especially in the social and economic fields. Thus, the government has taken an action by launching a family planning program to control the rate of population growth. One of the most popular family planning programs is the 3-month injection KB with side effects. This study aimed to determine the effect of the provision of communication, information, and education regarding the side effects of using a 3-month injection of KB on the level of knowledge of family planning acceptors about the side effects of using KB in BPM L in Banjaranyar village. This was comparative research with a quantitative approach. The number of samples was 15 respondents in both the intervention group and the control group. In addition, the data were collected using a questionnaire and were analyzed using the Fisher test. The result showed that there were 15 respondents (100%) in the intervention group with good predicate, while the level of knowledge in the control group with good predicate was 8 respondents (53%) and 7 respondents (40%) not good predicate. Then the P-value obtained from the Fisher test was 0.006, so the p-value was 0.05. There was an effect of the provision of communication, information, and knowledge regarding the side effects of using 3-month injectable contraceptives on the level of knowledge of family planning acceptors in BPM midwives in Banjaranyar village.